Perancangan Bisnis Untuk Jasa Fotografi Bayi Kita Photolier - Kathleen Angelita Kurniawan; Marina Wardaya (Jurnal Vicidi, 2018)
The research concept of baby and family photography business is done with the aim to describe the design of family photography business that provides baby and family photography services by cooperating with the second party that is maternity hospital. The purpose of this study is useful to determine consumer desires, market needs, and business design strategies in accordance with our photography services Photolier. The research method used is qualitative method with interview and quantitative method by dividing the questionnaire to prospective customers who domicile in surabaya. The conclusion of the research result is that infants and children are currently interested in already existing competitors who first started this business.